Social Economic Mapping of Tilapia Farmer Communities at Lengkong Kulon Village Sindangwangi District Majalengka Regency - Fajarwati, Mayapada; Andriani, Yuli; Suryana, Asep Agus Handaka; Maulina, Ine (Torani Journal of Fisheries and Marine Science, 2023)
This study aims to compile socio-economic mapping and analyze socio-economic factors that influence tilapia farmer communities. The research was conducted from January 2023 to March 2023 in Lengkong Kulon Village, Sindangwangi District, Majalengka Regency. The method used is the survey method. Sampling using the purposive sampling technique was analyzed with descriptive qualitative. The results of the mapping are grouped into two aspects, namely social conditions and economic conditions. The social condition of fish farmers is that they are of productive age with a low level of education. Livelihoods as fish farmers are part-time. The aquaculture business is mostly done by men as breadwinners, while women play a role in carrying out domestic activities, the role of women in fish farming is only to help provide feed. The social stratification of the fish farmer community is in the lower strata as ordinary people. Farmers generally have a strong kinship based on family ties. The economic conditions of most fish farmers have income that is in the low category, which is less than IDR 5,000,000 per month. Social factors that hinder fish farming in developing their business are lack of counseling, lack of training, and livelihoods as fish farmers are part-time so they are not serious about carrying out the fish farming business. The economic factors that hinder fish farmers are the high prices of feed and seeds.